Microstructure evolution and superelastic behavior in Ti-35Nb-2Ta-3Zr alloy processed by friction stir processing. (1st June 2017) - Wang, Liqiang; Xie, Lechun; Lv, Yuting; Zhang, Lai-Chang; Chen, Liangyu; Meng, Qiang; Qu, Jiao; Zhang, Di; Lu, Weijie
Abstract: This work investigates systematically the phase transformation and superelasticity in TiNbTaZr alloy prepared by friction stir processing (FSP). Multiple-pass FSP with a 100% accumulated overlap to three passes was implemented. The influence of the processing parameters on the microstructural evolution and superelasticity in stir zone, transition zone, and heat affected zone were investigated. After recrystallization, existing dislocations gradually accommodate themselves at sub-grain boundaries. Increase in the proportion of α″ martensitic phase is always accompanied by significant reduction in the fraction of ω phase precipitation. Metastable ω phase dissolving feature is evident and promoted by dislocation gliding, especially in the specimen processed at a higher rotation speed. In nanoindentation measurements, the closer the indent applied towards the transition zone, the more martensites nucleate, thereby gradually reducing both elastic modulus and hardness via re-orientation of martensites. This study provides new insight into the surface modification of beta titanium alloys through FSP method to achieve improved mechanical properties. Graphical abstract: Image 1